Numerical modeling for optimized sediment deflection with variable submergence over a row of submerged vanes - Vikalp Chauhan; Ellora Padhi; Gopal Das Singhal (Discover Applied Sciences)
Abstract Submerged vanes, functioning as in-stream hydrodynamic devices, are crucial in deflecting sediments across the flow of rivers, thereby contributing to sediment management and applications in river engineering. Although arrays of submerged vanes are frequently employed under conditions of constant submergence, the advantages of implementing variable vane heights or submergence levels across a row remain unexamined. This research examines the potential for improved sediment deflection efficiency through the optimisation of variable submergence. Multiple configurations of a row of four rectangular vanes with varying heights were tested to analyse their impact on secondary circulation strength and sediment deflection downstream. We conducted an analysis of the flow field surrounding and extending beyond the submerged vanes utilising the Flow-3D Hydro numerical model. The findings demonstrate that configurations exhibiting greater submergence towards the riverbank significantly enhance sediment deflection. Quantitative analysis shows that the configuration featuring vane heights that decrease toward the bank (HDTB1) achieves a 27% higher secondary circulation strength in the y–z plane compared to the configuration where vane heights remain constant toward the bank (HCTB). Additionally, the configuration HDTB1 yields a 39.4% higher moment of momentum in the near-bed region compared to HCTB. The results provide significant insights for river engineering, indicating that variable submergence designs may serve as an effective approach for enhanced sediment management in both natural and engineered waterways. Article Highlights The HDTB1 configuration, with decreasing vane height towards the channel bank, enhances vortex strength, improving sediment deflection. Increased transverse shear stress and turbulent energy in the HDTB1 setup promote erosion in suction zones and sediment deposition in pressure zones, improving the productivity of transverse slope formation. Optimized vane design enhances secondary flow and vorticity, offering efficient, cost-effective solutions for sediment management in river training applications.